Smartness that matters: towards a comprehensive and human-centred characterisation of smart cities - Alexander Prado Lara; Eduardo Moreira Da Costa; Thiago Furlani Zilinscki; Tan Yigitcanlar (Journal of Open Innovation: Technology, Market, and Complexity, 2016)
The term "smart cities" is a widely used, but at the same time a highly fuzzy concept. The fuzziness hinders our understanding on the benefits of its adoption, and explains the existence of many relevant activities with fragmented or distorted views of what a truly smart city is. The aim of this paper is to undertake a comprehensive review of how smart cities are perceived in the literature and in the light of the findings propose a clearer definition. Overview of the key terms, concepts and definitions associated to smart cities, reported in this paper, demonstrates that the definitions found in the academic literature have limited scope, and are overly focused on strategic drivers and specific actions, instead of making explicitly the connection between the concept of smart cities and the creation of environments that promote happiness and wellbeing of their residents-which should be the main function of a city. Following the thorough review on the smart cities literature, the paper proposes a comprehensive, human-centred, and context-free definition for smart cities. This definition brings an endogenous view on smart cities in which the central element is the direct participation of local actors and stakeholders in the process of thinking, defining, planning, and executing social, technological and urban transformations in cities.
Keywords: 650; Smart cities; Smart communities; Smart urban technologies; Innovation; Human-centred cities; Urban planning and development